2012
DOI: 10.1017/jfm.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of vortices in a turbulent boundary layer

Abstract: The motion of spanwise vortical elements and large-scale bulges has been tracked in the outer region between wall-normal distance z/δ = 0.11 and 0.30 of a turbulent boundary layer at Re θ = 2460. The experimental dataset of time-resolved threedimensional velocity fields used has been obtained by tomographic particle image velocimetry. The tracking of these structures yields their respective average trajectories as well as the variations thereof, quantified by the root mean square of the trajectory coordinates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
8
31
0
Order By: Relevance
“…We therefore conjecture that large scale regions on average grow slowly, i.e., with the same order of magnitude as the average boundary layer growth rate. Furthermore, it is worth mentioning that the boundary entrainment velocity of the average shear layer at y/δ 99 = 0.2 (E b ≈ 0.003U ∞ ) shows a correspondence with the work of Elsinga et al, 44 who found the average wall-normal convection velocity of spanwise vortices to be 0.006U e ± 0.002U e . Assuming these vortices populate the shear layers, this correspondence with the motion of instantaneous vortex structures supports the present conditional averaging approach.…”
Section: Discussionsupporting
confidence: 85%
“…We therefore conjecture that large scale regions on average grow slowly, i.e., with the same order of magnitude as the average boundary layer growth rate. Furthermore, it is worth mentioning that the boundary entrainment velocity of the average shear layer at y/δ 99 = 0.2 (E b ≈ 0.003U ∞ ) shows a correspondence with the work of Elsinga et al, 44 who found the average wall-normal convection velocity of spanwise vortices to be 0.006U e ± 0.002U e . Assuming these vortices populate the shear layers, this correspondence with the motion of instantaneous vortex structures supports the present conditional averaging approach.…”
Section: Discussionsupporting
confidence: 85%
“…It can be observed that the swirling strength increases until ∆t + = 0, i.e, the time at which the event was specified, and then decreases steadily with increasing time. This decreasing strength corresponds to a loss of correlation with increasing time shifts, which can be attributed to variations in convection velocities of the structures considered in the averaging [3]. Similarly, figure 4 shows that the peak negative Reynolds shear stress, normalized by its value at ∆t + = 0, increases until ∆t + = 0 and then decreases.…”
Section: Resultsmentioning
confidence: 90%
“…They have also highlighted examples of vortex structures merging or splitting [2,3,8]. When presenting structural interactions, only the (small-scale) vortices were included in the discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Following two decades of experimental and numerical work in wall-bounded turbulent flows, as reviewed in Marusic et al (2010), today's experiments by tomographic particle image velocimetry (PIV) have allowed for unprecedented volumetric and time-resolved measurement of such flows (Schröder et al 2008(Schröder et al , 2011Elsinga and Marusic 2010;Elsinga et al 2012). Recent studies have, however, stumbled upon the spatial resolution limitations of tomographic PIV for measurements in a turbulent flow (Atkinson et al 2011;Kähler et al 2012;Lynch et al 2014).…”
Section: Introductionmentioning
confidence: 99%